Apakah Aktivitas Ketarunaan Mempengaruhi Performa Terbang Malam? - Wicaksono, Agung Wahyu; Arif Fathurrohman, Satrio; Rachman, M. Arief (Langit Biru: Jurnal Ilmiah Aviasi, 2024)
Night flying training is one of the training stages that pilot cadets must take. Night flying training is full of risks because apart from dark conditions, pilot cadets also carry out activities all day long, and the possibility of fatigue and tiredness is greater. This research aims to measure the night flying performance of pilot cadets by using cadet activities as the independent variable. Fatigue is also used as an intervening variable in this research so that it can provide a complete image of night flying performance. This research uses quantitative methods with SEM-PLS analysis using the SmartPLS3 application. The research results showed that cadet activity had an influence on night flying performance while fatigue had no influence on night flying performance. Meanwhile, cadet activities do not have an influence on fatigue of pilot cadets